2018
DOI: 10.1371/journal.pone.0200878
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic cell death associated to Sorafenib in renal cell carcinoma is mediated through Akt inhibition in an ERK1/2 independent fashion

Abstract: ObjectivesTo fully clarify the role of Mitogen Activated Protein Kinase in the therapeutic response to Sorafenib in Renal Cell Carcinoma as well as the cell death mechanism associated to this kinase inhibitor, we have evaluated the implication of several Mitogen Activated Protein Kinases in Renal Cell Carcinoma-derived cell lines.Materials and methodsAn experimental model of Renal Cell Carcinoma-derived cell lines (ACHN and 786-O cells) was evaluated in terms of viability by MTT assay, induction of apoptosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…The apparent defect in the ATG12-dependent conjugation system was associated with decrease autophagic flux, in accordance with the role for this ubiquitin-like protein conjugation system in autophagosome formation and expansion 38,39 . Considering the impact autophagy can have on cancer cells survival or dismiss 54 , targeting the autophagy process has been considered as potential therapeutic strategy to combat various type of tumors, including in patient with ccRCC [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent defect in the ATG12-dependent conjugation system was associated with decrease autophagic flux, in accordance with the role for this ubiquitin-like protein conjugation system in autophagosome formation and expansion 38,39 . Considering the impact autophagy can have on cancer cells survival or dismiss 54 , targeting the autophagy process has been considered as potential therapeutic strategy to combat various type of tumors, including in patient with ccRCC [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, interventions to both stimulate and inhibit autophagy have been proposed as cancer therapies 19 . Likewise, inhibition and induction of autophagy have both been considered as therapeutic strategies to combat RCC [20][21][22][23][24] . Additional studies suggest that autophagic gene polymorphisms are associated with ccRCC risk and patient outcome 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy activation insures and protects cancer cells, and this process in known as adaptive autophagy, which is directly associated with CDK5. Cancer cells subjected to chemotherapy treatments have the ability to induce autophagic cell death through the inhibition of Akt [108]. Recent studies have showed that autophagy could be regulated using anticancer drugs.…”
Section: Function Of Cdk5 In Autophagymentioning
confidence: 99%
“…However, severe activation of autophagy, known as maladaptive autophagy, could directly induce cell death [1720]. Therefore, the level of autophagy is strictly controlled by various signaling pathways, such as PI3K/Akt/mTOR and ERK1/2 [23]. Blockade of autophagy in many cancers (including renal cancer cells) induces the exhaustion of metabolic substrates and causes energetic impairment, which eventually leads to cell death [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cancer cells are able to activate autophagy when exposed to chemotherapy drugs [2022]. In renal cancer, sorafenib could induce autophagic cell death through Akt inhibition [23]. However, blocking autophagy with chloroquine enhances the anticancer effect of sunitinib [24].…”
Section: Introductionmentioning
confidence: 99%